Water quality analysis based on the presence of aquatic macroinvertebrates applied to water springs covered with soil-cement technique - Mallet, Eduardo Rodrigo Viana; Nascimento, Elynton Alves do; Martins, Kelly Geronazzo; Oliveira Filho, Paulo Costa de (Revista Brasileira de Ciência, Tecnologia e Inovação, 2023)
Human activities, such as deforestation and inappropriate waste disposal have had negative impact on watercourses, including water spring areas. The soil-cement technique is a low-cost and easily implementable option to safeguard water springs and to preserve watercourses. The aim of the preset study is to assess water quality in water springs in Prudentópolis City, Brazil by using this technique based on aquatic macroinvertebrate communities and land use in this location. In total, 1,236 macroinvertebrates belonging to 18 taxa were collected from 5 water springs. Species belonging to family Chironomidae prevailed in points A, B, C and E, since they represent approximately 42% of all collected insects. Tree Cover was the primary land use form in the assessed points. According to Canonical Correspondence Analysis (CCA), different taxonomic groups had different responses to the assessed environmental factors. In conclusion, soil preservation, sustainable management and the cement technique, in combination to a set of preventive actions, were effective measures to ensure the conservation of aquatic ecosystems and water quality.